Custom‐made 3D printed subperiosteal implant for restoration of severe atrophic jaw: A case report - Luminita Nedelcu; Ioan Sirbu; Valentin Daniel Sirbu; Andreea Mihaela Custura; Adelin Radu; Vladimir Nastasie (Clinical Case Reports)
Key Clinical Message Digital technology significantly enhances subperiosteal implantology by enabling precise presurgical planning based on CBCT scans. This technology reduces patient trauma and ensures optimal implant fit, presenting a promising alternative to traditional analogue methods. Abstract In the last decades, significant progress has been made in oral implantology, particularly with endosseous implants, primarily due to advancements brought about by the digital revolution. Although their versatility and predictability have been well‐documented through clinical studies and follow‐ups (J Periodontol, 2005; 769: 1623), endosseous implants have certain limitations from the patients' perspectives, such as general health status, bone availability, and lengthy osseointegration times. Researchers have reported that well‐designed subperiosteal implants function successfully for many years and are a viable alternative to endosseous implants. The analogue method of inserting subperiosteal implants has been extensively discussed and utilized, and it represents a well‐defined protocol (Int J Sci Res, 2016; 5: 98). However, the surgical step, which involves taking an impression of the residual bone, posed challenges for clinicians. These challenges included more significant trauma to the patient, who had to undergo two surgical interventions instead of one (first for the bone impression and second for the implant insertion) and the risk of implant misfit due to the contraction of the impression material. Digital technology addresses these issues by allowing clinicians to design the implant based on the patient's Cone Beam Computed Tomography (CBCT) scan long before surgery. This case report reviews the design characteristics of 3D‐printed superiosteal implants, outlines the step‐by‐step procedure, and highlights the specific features compared to the analogue method. It also discusses the anatomy of the areas where the implants rest in the maxillae based on recent research performed in Romania in collaboration with AB Dental International (J Oral Implantol, 2003; 29: 189).